Catalytic activity atlas of ternary Co–Fe–V metal oxides for the oxygen evolution reaction. Issue 31 (16th June 2020) - Chen, Junsheng; Li, Hao; Pei, Zengxia; Huang, Qianwei; Yuan, Ziwen; Wang, Chaojun; Liao, Xiaozhou; Henkelman, Graeme; Chen, Yuan; Wei, Li
Abstract : Accurate composition–oxygen evolution reaction performance atlases have been established for a ternary Co–Fe–V oxide system using Prussian blue analogues as precursors, affording Co : Fe : V = 3 : 4 : 3 as the optimal metal ratio. Abstract : The sluggish oxygen evolution reaction (OER) is a crucial limiting factor in many renewable energy conversion and storage devices. Multi-metal oxides have been explored as efficient electrocatalysts for the OER; however, the ideal elemental composition for multi-metal oxides is unknown. We first performed density functional theory calculations, which predicted that Co oxyhydroxides doped with Fe and V have excellent catalytic activity. We synthesized a series of amorphous Co–Fe–V ternary metal oxides with a precisely controlled metal molar composition (denoted as Co a Fe b V c O x, where a + b + c = 10), uniformly distributed elements and identical morphologies by using Prussian blue analogues (PBAs) as novel metal precursors. A systematic investigation was carried out to establish correlations between the elemental compositions and the OER activity for Co a Fe b V c O x, resulting in a comprehensive catalytic activity atlas of ternary Co–Fe–V metal oxides for the OER, which can serve as a roadmap for electrocatalyst development. In particular, Co3 Fe4 V3 O x with an elemental composition of Co : Fe : V = 3 : 4 : 3 shows the best performance, with an overpotential of merely 249 mV to reach a current density of 10 mA cm −2, and a low Tafel slope of 41 mV dec −1, outperforming a commercial IrO x catalyst. X-ray photoelectron spectroscopy analysis reveals strong electronic synergies among the metal cations in Co a Fe b V c O x . The V and Fe doping can affect the electronic structure of Co to yield nearly optimal adsorption energies for OER intermediates, giving rise to the superior activity. Furthermore, composition-tuneable and uniform PBAs may serve as versatile and efficient metal precursors to produce many more multi-metal oxides for various renewable energy applications.